Should It Be Easier or Harder to Use Unapproved Drugs and Devices? - Flannery, Ellen J. (The Hastings Center report, 1986)
In applying statutory safeguards, the FDA must not regulate investigational new products so stringently that a life-saving therapy is unavailable. But the agency must also protect dying patients from exploitation by unscrupulous or overzealous researchers. The balance between individual choice and public protection has been questioned in cases involving experimental AIDS drugs and an artificial heart.